Setting the priorities for action: Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Pandya-Lorch, Rajul (International Food Policy Research Institute, 2001)
Pandya-Lorch sets forth the goal of the conference as influencing and catalyzing action to achieve sustainable food security for all by 2020." She describes the conference structure and program and the reasons for coming together to examine priorities of action and improve understanding of roles and responsibilities."